Evaluating Qur’anic Learning in Intensive Religious Programs: An Integrative Perspective on Non-Formal Islamic Education - Rahil Annisa; Maya Safitri (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to examine and conceptualize the evaluation of Qur’anic learning within intensive religious programs by analyzing how evaluation practices are implemented as an integrated system in non-formal Islamic education settings. This study employs a qualitative approach using a case study design to gain an in-depth understanding of evaluation practices in a natural context. Data were collected through participant observation, semi-structured interviews, and document analysis involving teachers and students in a Ramadan intensive program. The data were analyzed using thematic analysis to identify patterns, categories, and overarching themes in evaluation practices. The findings reveal that Qur’anic learning evaluation is implemented through four interconnected forms: recitation (tilawah), tajwid, memorization (tahfidz), and tilawatil Qur’an evaluation. These forms are continuously integrated into daily learning through direct recitation, immediate feedback, structured memorization submission, and performance-based activities. The evaluation system reflects a combination of formative and authentic assessment, emphasizing real-time improvement, active learner engagement, and multidimensional skill development. Despite challenges such as limited time, diverse student abilities, and the absence of standardized instruments, evaluation practices remain effective due to intensive teacher–student interaction and adaptive instructional strategies. This study introduces an integrative evaluation perspective that bridges technical (recitation and tajwid), cognitive (memorization), and affective-aesthetic (tilawatil Qur’an) dimensions within a unified framework. It challenges the conventional assumption that evaluation in non-formal Islamic education is informal and fragmented by demonstrating its systematic and pedagogically embedded nature. This study contributes to the advancement of educational assessment theory by extending formative and authentic assessment frameworks into the context of Qur’anic learning. It provides a context-sensitive model of evaluation that can inform the development of more holistic and effective assessment practices in non-formal Islamic education. Additionally, it offers practical insights for educators in designing flexible, continuous, and meaningful evaluation systems that enhance learning quality.